The role of the iPad in collaborative learning in a large-enrollment first-year physics module. (14th June 2016) - van der Ventel, Brandon; Newman, Richard; Botes, Lise; Goldberg, Alan
Abstract: The role of the iPad was investigated in the possible enhancement of collaborative learning within a tutorial setting in a large-enrollment first-year physics module. Every tutorial session was divided into an 'iPad group' and a 'non-iPad group'. A set of core apps was chosen to facilitate discussion within the group. In order to maintain parity across the two groups, all the tutorial questions had to be refitted into a form suitable for use with the iPad. The results of a survey done after each tutorial indicates that, qualitatively, the iPad significantly enhanced the learning experience and strongly contributed to discussion within the group.